Combined Effects of Postharvest Heat Treatment and Modified Atmosphere on Quality of Fresh-Cut Melons and Mangoes - Charles, F.; Morgado, C. M. A. [UNESP]; Mattiuz, B. [UNESP]; Sallanon, H.; Terry, L. A.; Cools, K.; Alamar, M. C. (Int Soc Horticultural Science, 2015)
Melon (Cucumis melo L.) and mangoes (Mangifera indica L.) are highly appreciated by consumers, due to sensory attributes and nutritional content. Producing minimally processed fruits has a potential, because consumers look for freshness and convenience. However, fresh-cut processing increases the decompartmentalization of enzymes and substrates which causes browning, softening and decay. These changes, mainly controlled with low temperature storage and modified atmosphere packaging, are still problems with fresh-cut fruits. This work investigated the effect of combination of heat treatment with modified atmosphere packaging on the quality of fresh-cut melons and mangoes. Whole fruits were dipped in hot water (50 degrees C - 30 min), cooled, minimally processed and packaged in traditional polymeric film (oriented polypropylene, OPP) or biologically-based film (Poly lactic acid, PLA). The heat treatment improved the storage of both fresh-cut melons and mangoes even if the effect on respiration rate was different. The firmness was maintained due to the MAP. Combining MAP and heat treatment significantly reduced color change and oxidation enzyme activities. It can be concluded that heat treatment combined with MAP could be a good opportunity to preserve the quality of fresh-cut melons and mangoes.
Keywords: respiration rate; firmness; color; modified atmosphere packaging; biodegradable film